Trends in allogeneic transplantation for favorable risk acute myeloid leukemia in first remission: a longitudinal study of >15 years from the ALWP of the EBMT - Nagler, Arnon; Labopin, Myriam; Salmenniemi, Urpu; Wu, Depei; Blaise, Didier; Rambaldi, Alessandro; Reményi, Péter; Forcade, Edouard; Socié, Gérard; Chevallier, Patrice; von dem Borne, Peter; Burns, David; et al. (Bone marrow transplantation, 2024)
We assessed outcomes of allogeneic transplantation (HSCT) in favorable risk AML in CR1 over 3 time periods. 1850 patients were included, 2005 to 2009- 222, 2010 to 2014 -392, and 2015 to 2021-1236; 526 with t (8:21), 625 with inv (16), and 699 with NPM1mutFLT3WT. Patients transplanted in 2015-2021 were older (p < 0.0001) with more patients ≥60 years of age (p < 0.0001). The most frequent diagnosis in 2015-2021 was NPM1mutFLT3WT vs. t (8:21) in the 2 earlier periods, (p < 0001). Haploidentical transplants (Haplo) increased from 5.9% to 14.5% (p < 0.0001). Graft-versus-host disease (GVHD) prophylaxis with post-transplant cyclophosphamide (PTCy) was more frequent in 2015-2021 vs. the other 2 periods (p < 0.0001). On multivariate analysis, incidence of total chronic GVHD was reduced in HSCTs performed ≥2015 vs. those performed in 2005-2009, hazard ratio (HR) = 0.74 (95% CI 0.56-0.99, p = 0.046) and GVHD-free, relapse-free survival (GRFS) improved for patients transplanted from 2010-2014 vs. those transplanted in 2005-2009, HR = 0.74 (95% CI 0.56-0.98, p = 0.037). Other HSCT outcomes did not differ with no improvement ≥2015. LFS, OS, and GRFS were inferior in patients with t (8:21) with HR = 1.32 (95% CI 1.03-1.68, p = 0.026), HR = 1.38 (95% CI 1.04-1.83, p = 0.027) and HR = 01.25 (95% CI 1.02-1.53, p = 0.035), respectively. In conclusion, this retrospective analysis of HSCT in patients with favorable risk AML, transplanted over 16 years showed an increased number of transplants in patients ≥60 years, from Haplo donors with PTCy. Most importantly, 3-year GRFS improved ≥2010 and total chronic GVHD reduced ≥2015, with no significant change in other HSCT outcomes.
Keywords: dospělí; Female; alografty; Adult; mladý dospělý; ženské pohlaví; longitudinální studie; Adolescent; homologní transplantace; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; nukleofosmin; Graft vs Host Disease; retrospektivní studie; Remission Induction; Male; Nucleophosmin; Aged; Allografts; indukce remise; Young Adult; nemoc štěpu proti hostiteli; akutní myeloidní leukemie; Transplantation, Homologous; lidé středního věku; senioři; mužské pohlaví; Retrospective Studies; Middle Aged; mladiství; Leukemia, Myeloid, Acute; Longitudinal Studies; Humans